Potensi Pengembangan Pada Padepokan Ciliwung Condet - Ananda, Arsya Tri; Nugraha, Rizki Nurul; Januarty, Dena Fitria; Irsyad, Kevin Muhammad (Peneliti.net, 2023)
Padepokan Ciliwung Condet is located on Jl. H. Mursali, RT. 008/001, Balekambang, Kramat Jati, East Jakarta. Which is one of the Betawi Culture preservation villages where you can carry out various activities such as activities regarding the preservation of Betawi culture, river rafting along the Ciliwung river, painting, batik, and farming. The research method used is descriptive qualitative through interviews and observations with informants as well as research from previous journals to obtain the data and information needed to compile this research. This study aims to determine the condition and development of the tourism potential of the Ciliwung Condet Padepokan, with the holding of tourism development it will have an impact on the increasing number of people who will get a positive impact. The Ciliwung Condet Padepokan is also a Community Based Tourism (CBT) because it involves the local community to preserve Betawi culture and increase the effectiveness of river management, with an emphasis on planning and development in the management of the Condet Ciliwung hermitage.